Guía de planeación de recolección de Datos & Coordinación del trabajo de campo en investigaciones con estudiantes universitarios (2020)
I propose the creation of a guide for epidemiological studies applied to the context of university students and defined health outcomes. Likewise, it is a valuable and essential contribution for research in university communities such as Uniandina, since it not only explain the phases of the project cycle, but also provides a solution to specific needs derived from the distinctive aspects involved in the study of young adults, through the compilation of a set of specific and detailed recommendations, as well as their feasibility. In this way, it is hoped that it will be appropriate for managing research and ensuring that the application of these strategies for coordinating the project cycle in the context of a university student is efficient and meaningful for the fulfillment of the objectives of any project involving young undergraduate students.